Biomechanical disparities in pankration: A comparative computational analysis of ancient and contemporary techniques - Bourantanis Andreas G.; Nomikos Nikitas N.; Nikolaidis Pantelis T.; Yiannakopoulos Chris K.; Aggelousis Nikolaos G.; Wang Weijie W. (Biomedical Human Kinetics)
Study aim: The study analyzed biomechanical similarities and differences between ancient and modern sports techniques, focusing on pankration. It examined historical artifacts and modern pankration scenes to elucidate biomechanical developments over time.